2015
DOI: 10.3329/bjb.v43i3.21600
|View full text |Cite
|
Sign up to set email alerts
|

Selection parameters for fruit yield and related traits in chilli (Capsicum annuum L.)

Abstract: Thirty genotypes of chilli were evaluated in RBD with three replications at vegetable research farm, CHF, CAU, Pasighat, Arunachal Pradesh, India during kharif, 2011. Variability, correlation and path analysis were carried out to study the character association and contribution, respectively. Analysis of variance revealed significant differences among the genotypes for all traits. High PCV and GCV, heritability, genetic advance were observed for days to first flowering, plant height, number of seed per fruit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 7 publications
13
13
0
2
Order By: Relevance
“…These results are similar with the findings of Singh et al, (2013), Yatung et al, (2014), Pandit and Ahikary (2014), Janaki et al, (2015) and Patel et al, (2015) also found sufficient variations for these traits. The result of analysis of variance is presented in table 1.…”
Section: Resultssupporting
confidence: 83%
“…These results are similar with the findings of Singh et al, (2013), Yatung et al, (2014), Pandit and Ahikary (2014), Janaki et al, (2015) and Patel et al, (2015) also found sufficient variations for these traits. The result of analysis of variance is presented in table 1.…”
Section: Resultssupporting
confidence: 83%
“…Similar results were reported by Gupta et al, (2009), Ullah et al, (2011), Chattopadhyay et al, (2011), Kumar et al, (2012), and Yatung et al, (2014, for fruit weight, fruit yield per plant, number of fruits per plant, fruit length and number of branches per plant whereas Kumar et al, (2012) also reported the significant and positive correlation between fruit yield. Positive and significant correlation of fruit yield per plant was observed with days to 50% flowering at both genotypic and phenotypic level also been reported by Basavaraj (1997), Nandapuri et al, (1970), and Dhahiya et al, (1991.…”
Section: Resultssupporting
confidence: 85%
“…In the present study (Tables 4 and 5), for selected 15 characters, the traits such as number of fruits per plant (0.672, 0.865), fruit weight (0.295, 0.385), stalk length (0.294, 116) had strong direct positive effect on yield which is in agreement with Yatung et al, (2014), Pandit and Adhikary (2014), Patel et al, (2015), Mamatha et al, (2016) and Sharma and Sridevi (2016) at genotypic as well as phenotypic level. The biochemical parameter viz., ascorbic acid also has direct positive effect towards yield (0.223, 0.296) which is in consonance with Chattopadhyay et al, (2011), Vikram et al, (2014 and Patel et al, (2015).…”
Section: Path Coefficient Analysissupporting
confidence: 75%
“…Plant height at 90 DAT (0.952, 0.630), Plant height at 120 DAT (0.899, 0.556), Secondary branches at 90 DAT (0.985, 0.553), fruit weight (0.497, 0.490), stalk length (0.686, 0.488) and fruits per plant (0.989, 0.778) had significant and positive correlation with green Chilli yield per plant at genotypic and phenotypic level respectively. This is in tune with the research work conducted by Patel and Patel (2014), Yatung et al, (2014) and Dolkar et al, (2015), Patel et al, (2015), Sharma and Sridevi (2016), and Mamatha et al, (2016).…”
Section: Correlation Coefficient Analysissupporting
confidence: 69%